Gerindra Party Admin Communication Strategy on Tiktok and X Social Media - Laras Sang Dyah Pitaloka Pitaloka; Agusniar Dian Savitri (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
The aim of this research is to analyze the strategies for interacting with audiences implemented by the Gerindra Party admin in the context of political communication via social media TikTok and X (Twitter). Given the increasing use of social media as a political communication tool, this study investigates how political parties can use digital platforms to reach wider audiences, especially the younger generation. The research method used in this research is online observation of the Gerindra Party admin's response to uploaded content and interactions with the audience. The results show that the communication strategy on TikTok focuses on informational and persuasive approaches, using engaging audio-visual content and popular hashtags to increase engagement. Meanwhile, social media admin X implemented a more informed and responsive strategy by sharing infographics and responding quickly to user comments. A comparative analysis of the two platforms reveals that although the goals of political communication are similar, the approaches used are different, depending on the characteristics of each platform. The findings of this research highlight the effectiveness of political communication strategies in the digital era and demonstrate the importance of adapting to social media trends to build a positive image and increase public engagement. This study aims to provide practical information to political parties to develop more effective communication strategies on social media and to deepen understanding of the dynamics of political communication in the public sphere. Keywords: Communication Strategy, Politics, TikTok, X, Gerindra Party Admin